Inventory System Application Design (Case Study: Shirouoshien Online Shop) - Akhsani Taqwiym (SISFOTENIKA, 2022)
Current technological advances in the process of recording inventory are felt to be very necessary, especially if the recording is done manually. Shirouoshien is an online business, products are sold and offered online using social media. Shirouoshien's efforts to record products manually, often the data of incoming and outgoing goods is not recorded properly. The process carried out is that the goods arrive, then they are photographed, then the product is offered to consumers. Available products will be stored and will move if the product is sold. During the buying and selling process, the documentation of the number of products in the warehouse was not recorded properly. The problem that occurs in shirouoshien is because employees do not get information about the stock of goods available both in the warehouse and recorded online. The making of notes is sometimes not documented or even made, increasing the risk of damage or loss. Inventories of goods at Shirouoshien often experience stock differences. To overcome the problems in Shirouoshien, a website was designed using descriptive qualitative methods that aim to facilitate the documentation process both in terms of handling the process of printing notes, changing inventory data, searching for inventory data, making sales reports for a certain period, and other types of goods. Descriptive qualitative method is taking objects regarding the system of recording and data collection of goods inventory which is applied to the Shirouoshien online shop. With a qualitative approach, data on the entry and exit of goods can be found.